Prevalence of Post-traumatic Stress Disorder among the General Population of Karachi during COVID-19 Pandemic and its Associated Factors (Journal of Medicine, 2022)
Objective: Coronavirus pandemic has spread globally. It has affected people mentally and economically.These types of pandemics often lead to post-traumatic stress traumatic syndrome among people. Researchdata is needed to know the PTSD due to the coronavirus pandemic among the general population.Materials and Methods: This study is cross-sectional. Data was collected in 3 days from the generalpopulation of Karachi through an online questionnaire regarding age, gender, education, profession,precautionary measures, awareness related to COVID, satisfaction related to COVID, Health informationawareness. IESR scale was used to assess post-traumatic stress syndrome. A total of 241 respondentswere involved.Results: Moreover, 11.2% had partial PTSD, 4.1% had PTSD and 34.9% had PTSD high enough to suppressthe immune system. Among the respondents majority belong to age group 20 to 30, female, student,undergraduate, were aware of COVID, tested positive for COVID, knew someone tested positive forCOVID, applied precautionary measures, avoided going out, worried about your family members gettingCOVID, satisfied with health information available and were aware of health information available. Agegroup 20 to 30, Male gender, matric education level, housewives, tested positive for COVID, applyingprecautionary measures, applying social distancing, having present physical symptoms, worrying aboutyour family members getting COVID, was associated with high IESR score and PTSD (p